THE CENTURY OF MULTILANGUAGES AS AN ADVANTAGE OF MODERN SOCIETY - Kallibekova, G.A. (SCIENCE and SOCIETY, 2026)
The article examines the phenomenon of multilingualism as an important advantage of modern society. It presents an analysis of the cognitive, cultural, educational, and economic aspects of multilingual competence. Particular attention is paid to the language policies of the CIS countries, including Uzbekistan, and to multilingual educational practices. It is shown that multilingualism contributes to personality development, intercultural competence formation, and competitiveness in the labor market.
Keywords: multilingualism; bilingualism; language policy; education; cognitive development; Uzbekistan; CIS